Medication-related osteonecrosis of the jaw with SPECT/CT: comparison of mandibular cortical morphology using computer-aided detection with dental panoramic imaging - Yuka Tanabe; Ichiro Ogura (Egyptian Journal of Radiology and Nuclear Medicine, 2026)
Abstract Background To date, dental panoramic radiography, CT, MRI and SPECT/CT are usability for evaluating medication-related osteonecrosis of the jaw (MRONJ). This study aimed to examine the MRONJ with SPECT/CT, especially comparison of mandibular cortical morphology using computer-aided detection with dental panoramic imaging. Methods Seventy-two MRONJ patients with Stage 2 in the mandible (26 bone metastases and 46 osteoporosis) underwent dental panoramic radiography and bone SPECT/CT. Mandibular cortical index (MCI) and degree of deformation as mandibular cortical morphology were evaluated with a software for dental panoramic imaging. Maximum standardized uptake value (SUVmax) using bone SPECT/CT of the lesions and normal mandible as control was obtained by a workstation and software. Results Regarding mandibular cortical morphology, degree of deformation in osteoporosis and bone metastases were 52.1 ± 21.5 and 35.8 ± 18.1, respectively ( p = 0.002). MCI class 3 in osteoporosis and bone metastases were 94.4–5.6%, respectively ( p = 0.002). Regarding SPECT/CT SUVmax, lesions in osteoporosis and bone metastases were 17.0 ± 6.5 and 13.8 ± 5.8, respectively ( p = 0.031), and control in osteoporosis and bone metastases were 5.4 ± 1.9 and 4.2 ± 1.4, respectively ( p = 0.007). Furthermore, the degree of deformation was not correlated with SPECT/CT SUVmax of MRONJ ( R 2 = 0.051, p = 0.055). Conclusion This study indicated that the SPECT/CT and mandibular cortical morphology in MRONJ was different between bone metastases and osteoporosis, and the data may be effective for the management in MRONJ patients with Stage 2 in the mandible.